Դատաստանական գործը Արցախի մելիքություններում - Հովսեփյան, Վլադիմիր (ԱրՊՀ հրատ․)
Автор в своей статье анализирует роль и место судопроизводства в Меликствах Арцаха. Подчеркнув особый юридический статус этого княжества, автором детально анализируются как форма и процесс судопроизводства, а также виды наказания и условия их назначения. In his article the author analyzes the role and the place of the proceedings in the principalities of Artsakh. Emphasizing the special legal status of this principality, the author examines in detail the shape and the process of proceedings, as well as penalties and conditions of their appointment.
Keywords: Պատմություն; Արցախի մելիքություններ (Խամսայի մելիքություններ); Արցախ